2015
DOI: 10.1097/tp.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Use of Generic Tacrolimus in Elderly Renal Transplant Recipients

Abstract: Generic tacrolimus (Tacni) was not found to be bioequivalent to the original formulation in elderly renal transplant recipients. The significantly higher systemic exposure of tacrolimus, despite similar trough concentrations, may in the long run increase the risk of adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…There were three crossover (25 patients de novo KT, 139 patients conversion LT and KT) and two parallel design studies (79 patients de novo KT), all RCTs, reporting the primary pharmacokinetic outcome of C max and AUC 0–12 (Fig. ) . Three prospective randomized pharmacokinetic studies in KT were conducted with de novo generic Tac (one study including a crossover substudy), and one after conversion .…”
Section: Resultsmentioning
confidence: 99%
“…There were three crossover (25 patients de novo KT, 139 patients conversion LT and KT) and two parallel design studies (79 patients de novo KT), all RCTs, reporting the primary pharmacokinetic outcome of C max and AUC 0–12 (Fig. ) . Three prospective randomized pharmacokinetic studies in KT were conducted with de novo generic Tac (one study including a crossover substudy), and one after conversion .…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, the only generic tacrolimus study specifically evaluating generic tacrolimus in the elderly was published. 59 This prospective, single-center, randomized, crossover trial evaluated the pharmacokinetic parameters of a generic tacrolimus (Tacni; Teva Pharmaceutical Industries, Petah Tikva, Israel) in 25 renal transplant recipients older than 60 years. Patients were randomized to receive either brand or generic tacrolimus at the time of transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Some excipients can alter the activity of efflux pumps that remove lipophilic molecules from the intracellular space. Sandimmune capsules (where the active component is dissolved in olive oil) were not bioequivalent to Sandimmune solution (where the active compo- Retrospective study in de novo renal transplant recipients (n = 188) [16] Pharmacokinetics not reported Acute rejections increased with Gengraf vs. Neoral (39 vs. 25%) [16] Gengraf patients more likely to receive antibody preparations to treat acute rejections (19 vs. 8%) [16] No difference in 12 h cyclosporin levels between Gengraf vs. Neoral groups [16] Graft and patient survival similar in both groups [16] Robertsen et al [19], 2015…”
Section: Discussionmentioning
confidence: 99%